Adolescents’ experiences with substance use: risks, protective factors and interventions - Mahsum Avcı (BMC Psychology)
Abstract Background This study aimed to explore adolescents’ experiences with substance use and to identify risk, preventive, and protective factors, as well as the intervention processes from their perspective. Methods Adopting a phenomenological qualitative approach, in-depth semi-structured interviews were conducted with 21 adolescents (ages 14–18) who had been using substances (excluding cigarettes and alcohol) for over one year. Participants were selected using criterion and snowball sampling methods. The data were analyzed through thematic analysis. Results Analysis revealed four main themes and twelve sub-themes: Risk Factors (including peer influence, family dysfunction, and trauma/psychosocial adversity). Preventive Factors (such as adolescent awareness, family recognition, and school-based teacher leadership). Protective Factors (including social skills, intrinsic/extrinsic motivation, and positive family interaction). Interventions (involving parent education, psychosocial interventions, and psychotherapies). Finding Findings indicated that adolescents’ substance use is influenced by complex individual, familial, and environmental interactions. Moreover, the results highlight that both international literature and literature from Turkey converge in showing the negative biopsychosocial impacts of substance use among youth. Conclusion The study underscores the multifaceted nature of substance use among adolescents, pointing to the importance of developing culturally informed, multi-level interventions that target risk, reinforce protective mechanisms, and enhance access to treatment.